2018
DOI: 10.1186/s40649-018-0059-5
|View full text |Cite
|
Sign up to set email alerts
|

Network partitioning algorithms as cooperative games

Abstract: The paper is devoted to game-theoretic methods for community detection in networks. The traditional methods for detecting community structure are based on selecting dense subgraphs inside the network. Here we propose to use the methods of cooperative game theory that highlight not only the link density but also the mechanisms of cluster formation. Specifically, we suggest two approaches from cooperative game theory: the first approach is based on the Myerson value, whereas the second approach is based on hedon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Inspired by path-discounting characteristic functions of Jackson and Wolinsky, 1996;Jackson, 2010, in Mazalov andTrukhina, 2014;Mazalov et al, 2016 for trees andin Avrachenkov et al, 2018a for general graphs, the following characteristic function was proposed. Let δ ∈ [0, 1] be a discount factor.…”
Section: Game Theory Based Centrality Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by path-discounting characteristic functions of Jackson and Wolinsky, 1996;Jackson, 2010, in Mazalov andTrukhina, 2014;Mazalov et al, 2016 for trees andin Avrachenkov et al, 2018a for general graphs, the following characteristic function was proposed. Let δ ∈ [0, 1] be a discount factor.…”
Section: Game Theory Based Centrality Indicesmentioning
confidence: 99%
“…In Avrachenkov et al, 2018a it was shown that this characteristic function leads to a manageable expression for the Myerson value:…”
Section: Game Theory Based Centrality Indicesmentioning
confidence: 99%
“…Finally, the third class of methods to network partitioning is based on the optimization of some objective such as likelihood [8,9], modularity [10] or energy function [11,12]. Interestingly, many mentioned approaches can also be viewed as particular instances of hedonic game [13]. The approach developed in this paper is also based on the energy function optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Graph clustering problems can be treated as cooperative games with a Nash stable coalition partition when none of the players benefit from changing the coalition structure. In this case, the Myerson value is used as an allocation principle; see [17,18].…”
Section: Introductionmentioning
confidence: 99%